Bis(phenylethynyl)arene Linkers in Tetracationic Bis‐triarylborane Chromophores Control Fluorimetric and Raman Sensing of Various DNAs and RNAs. Issue 16 (24th February 2021) - Ferger, Matthias; Ban, Željka; Krošl, Ivona; Tomić, Sanja; Dietrich, Lena; Lorenzen, Sabine; Rauch, Florian; Sieh, Daniel; Friedrich, Alexandra; Griesbeck, Stefanie; Kenđel, Adriana; Miljanić, Snežana; et al.
Abstract: We report four new luminescent tetracationic bis‐triarylborane DNA and RNA sensors that show high binding affinities, in several cases even in the nanomolar range. Three of the compounds contain substituted, highly emissive and structurally flexible bis(2, 6‐dimethylphenyl‐4‐ethynyl)arene linkers (3 : arene=5, 5′‐2, 2′‐bithiophene; 4 : arene=1, 4‐benzene; 5 : arene=9, 10‐anthracene) between the two boryl moieties and serve as efficient dual Raman and fluorescence chromophores. The shorter analogue 6 employs 9, 10‐anthracene as the linker and demonstrates the importance of an adequate linker length with a certain level of flexibility by exhibiting generally lower binding affinities than 3 –5 . Pronounced aggregation–deaggregation processes are observed in fluorimetric titration experiments with DNA for compounds 3 and 5 . Molecular modelling of complexes of 5 with AT‐DNA, suggest the minor groove as the dominant binding site for monomeric 5, but demonstrate that dimers of 5 can also be accommodated. Strong SERS responses for 3 –5 versus a very weak response for 6, particularly the strong signals from anthracene itself observed for 5 but not for 6, demonstrate the importance of triple bonds for strong Raman activity in molecules of this compound class. The energy of the characteristic stretching vibration of the C≡C bonds is significantly dependent on the aromatic moiety between the triple bonds. The insertion of aromatic moieties between two C≡C bonds thus offers an alternative design for dual Raman and fluorescence chromophores, applicable in multiplex biological Raman imaging. Abstract : Aromatic alternative : Four bis‐triarylborane chromophores with high binding affinities to DNA and RNA are reported. Three of them employ bis(phenylethynyl)arene linkers and are strongly fluorescent and highly Raman active. Fluorimetric titration experiments reveal distinct aggregation–deaggregation processes for two of the compounds, and molecular modelling of complexes of the compounds with DNA illustrates and corroborates the experimental findings.